Towards sustainable plant factories with artificial lighting (PFALs) for achieving SDGs - Kozai, Toyoki (International Journal of Agricultural and Biological Engineering, 2019)
The challenges and opportunities for developing sustainable plant factories with artificial lighting (PFALs) are discussed. After examining the production cost and productivity of existing PFALs in Japan, the possibility of introducing a relatively new concept and methodology for considerably improving productivity are discussed in relation to environmental controllability and resource use efficiencies. The fundamental and potential characteristics of ideal or next-generation PFALs (n-PFALs) are then discussed with some suggestions for actualizing n-PFALs. Finally, perspectives of the n-PFALs and technologies to be integrated into the n-PFALs are presented in relation to the Sustainable Development Goals (SDGs) to be achieved by 2030.Keywords: plant factory with artificial lighting (PFAL), productivity, production cost, SDGsDOI: 10.25165/j.ijabe.20191205.5177Citation: Kozai T. Towards sustainable plant factories with artificial lighting (PFALs) for achieving SDGs. Int J Agric & Biol Eng, 2019; 12(5): 28–37.